Lithium-ion solid-state rechargeable battery
Patent Information
- Application Number
- JP2025060134
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2025-03-31
- Publication Date
- 2026-10-14
AI Technical Summary
【0022】 本発明によれば、短絡防止·耐久性向上といった電池セル性能と、強度·靭性といった構造成立性とが高いレベルでバランスよく向上したリチウムイオン固体二次電池を提供することが可能となる。
Smart Images

Figure 2026166895000001_ABST
Abstract
Description
[Technical Field]
[0001] This invention relates to a lithium-ion solid-state secondary battery. [Background technology]
[0002] In recent years, research and development has been conducted on rechargeable batteries that contribute to energy efficiency, in order to ensure that more people have access to affordable, reliable, sustainable, and advanced energy.
[0003] As such secondary batteries, lithium-ion solid-state batteries are known, which use lithium ions as a charge transfer medium and have a solid electrolyte layer placed between a positive electrode layer and a negative electrode layer. In lithium-ion solid-state batteries, it has been considered to use a two-layer laminate structure in which a first solid electrolyte layer placed on the positive electrode side and a second solid electrolyte layer placed on the negative electrode side are stacked. For example, it has been considered to set a predetermined relationship between the maximum height Rz1 of the surface of the first solid electrolyte layer on the side of the second solid electrolyte layer (first surface) and the maximum height Rz2 of the surface of the second solid electrolyte layer on the side of the first solid electrolyte layer (second surface) (Patent Document 1), to make the density of the first solid electrolyte layer greater than the density of the second solid electrolyte layer (Patent Document 2), and to use a sulfide-based solid electrolyte as the solid electrolyte and make the average particle size (D50) of the second sulfide-based solid electrolyte contained in the second solid electrolyte layer greater than the average particle size (D50) of the first sulfide-based solid electrolyte contained in the first solid electrolyte layer (Patent Document 3). [Prior art documents] [Patent Documents]
[0004] [Patent Document 1] Japanese Patent Publication No. 2023-009988 [Patent Document 2] International Publication No. 2024 / 111841 [Patent Document 3] Special Publication No. 2023-524296 [Overview of the Initiative] [Problems that the invention aims to solve]
[0005] In lithium-ion solid-state secondary batteries, the solid electrolyte layer is required to have multiple functions, including separation of the positive and negative electrode layers, prevention of lithium metal deposition, ion conduction, volume expansion mitigation, and cushioning. Furthermore, the solid electrolyte layer is also required to have high properties that contribute to structural integrity, such as strength and toughness. However, according to the inventors' research, it is difficult to satisfy the above functions and properties with a single-layer solid electrolyte layer. Moreover, it is difficult to satisfy the above functions and properties even when using a conventional two-layer solid electrolyte layer.
[0006] This invention has been made in view of the above, and aims to provide a lithium-ion solid-state secondary battery that has a high level of balance between battery cell performance, such as short-circuit prevention and improved durability, and structural integrity, such as strength and toughness. Ultimately, this will contribute to energy efficiency. [Means for solving the problem]
[0007] The inventors have found that, in order to address the above-mentioned problems, it is effective to have a laminate in which a first solid electrolyte layer is arranged on the positive electrode side and a second solid electrolyte layer is arranged on the negative electrode side, and to make the mass content of the solid electrolyte in the first solid electrolyte layer greater than the mass content of the solid electrolyte in the second solid electrolyte layer, thereby completing the present invention. Accordingly, the present invention provides the following.
[0008] (1) A lithium-ion solid-state secondary battery comprising a positive electrode layer, a negative electrode layer, and a solid electrolyte layer interposed between the positive electrode layer and the negative electrode layer, wherein the solid electrolyte layer is a laminate formed by laminating a first solid electrolyte layer disposed on the positive electrode layer side and a second solid electrolyte layer disposed on the negative electrode layer side, the first solid electrolyte layer contains a first solid electrolyte, the second solid electrolyte layer contains a second solid electrolyte, the ratio D50_2 / D50_1 of the average particle diameter D50_2 of the second solid electrolyte to the average particle diameter D50_1 of the first solid electrolyte is in the range of 1.0 or more and 50.0 or less, and the ratio W1 / W2 of the mass content W1 of the first solid electrolyte in the first solid electrolyte layer to the mass content W2 of the second solid electrolyte in the second solid electrolyte layer is in the range of more than 1.0 and 1.2 or less.
[0009] In the lithium-ion solid-state secondary battery of (1), the first solid electrolyte layer has a higher mass content of solid electrolyte compared to the second solid electrolyte layer, and the solid electrolytes adhere strongly to each other, resulting in high lithium-ion conductivity, high rigidity, and excellent shape stability, acting as a rigid layer. On the other hand, the second solid electrolyte layer can have a higher mass content of components other than solid electrolyte (e.g., binder) compared to the first solid electrolyte layer, resulting in high flexibility and ductility, making it easier to adhere to the first solid electrolyte layer and the negative electrode layer, resulting in high impact resistance, and acting as a soft layer with excellent ability to relieve strain applied to the second solid electrolyte layer. For this reason, the solid electrolyte layer formed by laminating the first and second solid electrolyte layers has excellent lithium-ion conductivity between the positive and negative electrode layers, as well as excellent shape stability and toughness. For this reason, the lithium-ion solid-state secondary battery of (1) achieves a high level of balance and improvement in battery cell performance, such as discharge characteristics and cycle characteristics, and structural integrity, such as shape stability and toughness.
[0010] (2) The lithium-ion solid secondary battery described in (1), wherein the ratio D50_2 / D50_1 is in the range of 2.0 or more and 10.0 or less.
[0011] In the lithium-ion solid-state secondary battery of (2), the first solid electrolyte is finer than the second solid electrolyte, and the contact area between the first solid electrolytes is larger, resulting in higher lithium-ion conductivity, higher rigidity and strength, and improved shape stability. On the other hand, the second solid electrolyte is coarser than the first solid electrolyte, and the gaps between the solid electrolytes are wider, resulting in higher flexibility and ductility, making it easier to bring the first solid electrolyte layer and the negative electrode layer into closer contact, resulting in higher impact resistance and improved ability to relieve strain applied to the second solid electrolyte layer. Therefore, the lithium-ion solid-state secondary battery of (2) achieves a higher level of balance between battery cell performance and structural integrity.
[0012] (3) The lithium-ion solid secondary battery according to (1) or (2), wherein the average particle size D50_1 of the first solid electrolyte is in the range of 0.1 μm or more and less than 1.0 μm, and the average particle size D50_2 of the second solid electrolyte is in the range of 1.0 μm or more and 5.0 μm or less.
[0013] In the lithium-ion solid-state secondary battery of (3), since the average particle diameter D50_1 of the first solid electrolyte and the average particle diameter D50_2 of the second solid electrolyte are within the above range, the first solid electrolyte layer has higher lithium-ion conductivity, higher rigidity and strength, and improved shape stability. On the other hand, the second solid electrolyte has further increased flexibility and ductility, making it easier to adhere more closely to the first solid electrolyte layer and the negative electrode layer, further increasing impact resistance, and further improving the ability to relieve strain applied to the second solid electrolyte layer. Therefore, the lithium-ion solid-state secondary battery of (3) achieves a better balance between battery cell performance and structural integrity.
[0014] (4) A lithium-ion solid-state secondary battery according to any one of (1) to (3), wherein the particle size D10_1 of the first solid electrolyte is less than 1.0 μm and the average particle size D90_2 of the second solid electrolyte is 5.0 μm or more.
[0015] According to the lithium ion solid secondary battery of (4), since the first solid electrolyte layer contains a large amount of fine solid electrolyte, the voids in the first solid electrolyte layer are filled with the solid electrolyte, so that the voids become fine. For this reason, the first solid electrolyte layer has further improved lithium ion conductivity. On the other hand, the second solid electrolyte layer contains a large amount of coarse solid electrolyte. Since the coarse solid electrolyte has a small specific surface area, the voids in the second solid electrolyte layer are coarser than the voids in the first solid electrolyte layer. As a result, the second solid electrolyte layer has higher impact resistance, and the ability to relax strain applied to the second solid electrolyte layer is further improved. Therefore, in the lithium ion solid secondary battery of (4), the battery cell performance and the structural integrity are improved in a well-balanced manner at a further higher level.
[0016] (5) The lithium ion solid secondary battery according to any one of (1) to (4), wherein the ratio S1 / S2 of the specific surface area S1 of the first solid electrolyte to the specific surface area S2 of the second solid electrolyte is in a range of 1.0 to 30.0.
[0017] According to the lithium ion solid secondary battery of (5), the first solid electrolyte has a larger specific surface area than the second solid electrolyte and contains a large amount of fine solid electrolyte, so that the voids in the first solid electrolyte layer become fine, and the lithium ion conductivity is further improved. On the other hand, since the second solid electrolyte layer contains a large amount of coarse solid electrolyte, the voids in the first solid electrolyte layer are coarser than the voids in the first solid electrolyte layer, and the ability to relax strain applied to the second solid electrolyte layer is further improved. Therefore, in the lithium ion solid secondary battery of (5), the battery cell performance and the structural integrity are improved in a well-balanced manner at a further higher level.
[0018] (6) The lithium ion solid secondary battery according to any one of (1) to (5), wherein the porosity P1 of the first solid electrolyte layer is less than 1%, and the porosity P2 of the second solid electrolyte layer is 1% or more.
[0019] According to the lithium ion solid-state secondary battery of (6), the first solid electrolyte layer has fewer voids than the second solid electrolyte layer, so that the first solid electrolyte layer has higher lithium ion conductivity, higher rigidity strength, and further improved shape stability. On the other hand, since the second solid electrolyte has more voids than the first solid electrolyte layer, it has higher flexibility and ductility, is more easily brought into close contact with the first solid electrolyte layer and the negative electrode layer, has higher impact resistance, and further improves the ability to relax strain applied to the second solid electrolyte layer. Therefore, in the lithium ion solid-state secondary battery of (6), battery cell performance and structural integrity are improved in a well-balanced manner at a higher level.
[0020] (7) The lithium ion solid-state secondary battery according to any one of (1) to (6), further comprising an intermediate layer between the solid electrolyte layer and the negative electrode layer.
[0021] According to the lithium ion solid-state secondary battery of (7), the interface between the negative electrode layer and the second solid electrolyte layer is stabilized, so that the battery cell performance is improved. Effects of the Invention
[0022] According to the present invention, it is possible to provide a lithium ion solid-state secondary battery in which battery cell performance such as short circuit prevention and durability improvement, and structural integrity such as strength and toughness are improved in a well-balanced manner at a high level. Brief Description of the Drawings
[0023] [Figure 1] It is a plan view of a lithium ion solid-state secondary battery according to an embodiment of the present invention. [Figure 2] It is a cross-sectional view taken along line II-II of Figure 1. [Figure 3] It is a cross-sectional view taken along line III-III of Figure 1. Modes for Carrying Out the Invention
[0024] Embodiments of the present invention will be described below with reference to the drawings. However, the embodiments shown below are illustrative of the present invention and are not limited to those shown below.
[0025] Figure 1 is a plan view of a lithium-ion solid-state secondary battery according to one embodiment of the present invention. Figure 2 is a cross-sectional view taken along line II-II of Figure 1, and Figure 3 is a cross-sectional view taken along line III-III of Figure 1.
[0026] As shown in Figures 1 to 3, the lithium-ion solid-state secondary battery 1 includes a positive electrode layer 2, a negative electrode layer 3, and a solid electrolyte layer 4 interposed between the positive electrode layer 2 and the negative electrode layer 3.
[0027] The positive electrode layer 2 comprises a positive electrode current collector 21, a positive electrode active material layer 22, and an insulating member 23. The positive electrode active material layer 22 is disposed on each of the two sides of the positive electrode current collector 21. The insulating member 23 is disposed on the surface of each of the two sides of the positive electrode current collector 21 and around the positive electrode active material layer 22. The positive electrode current collector 21 is connected to a positive electrode tab 21a. The positive electrode tab 21a extends in one direction (the X direction in Figure 1). The thickness of the positive electrode current collector 21 may be, for example, in the range of 0.1 μm to 1 mm. The thicknesses of the positive electrode active material layer 22 and the insulating member 23 may be, for example, in the range of 0.1 μm to 1 mm.
[0028] Examples of materials for the positive electrode current collector 21 include aluminum, aluminum alloy, stainless steel, nickel, iron, and titanium.
[0029] The positive electrode active material layer 22 contains a positive electrode active material. The positive electrode active material may be a lithium compound that releases lithium ions when the lithium-ion solid-state secondary battery 1 is charged and absorbs lithium ions when the lithium-ion solid-state secondary battery 1 is discharged. As lithium compounds, for example, layered active materials, spinel-type active materials, and olivine-type active materials can be used. Specific examples of positive electrode active materials include lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), and lithium nickel manganese cobalt oxide (NMC:LiNi p Mn qCo r O2(p+q+r=1), LiNi p Al q Co r O2 (p+q+r=1), lithium manganese (LiMn2O4), Li 1+x Mn 2-x-y Examples include heteroatom-substituted Li-Mn spinel represented by MO4 (x+y=2, M=at least one selected from Al, Mg, Co, Fe, Ni, and Zn), lithium titanate (oxide containing Li and Ti), and metallic lithium phosphate (LiMPO4, M=at least one selected from Fe, Mn, Co, and Ni). The positive electrode active material layer 22 may further contain materials that can be included in the positive electrode active material layer of a lithium-ion solid-state secondary battery, such as conductive additives, binders, and solid electrolytes.
[0030] Examples of materials for the positive electrode tab 21a include aluminum, aluminum alloy, stainless steel, nickel, iron, and titanium. The positive electrode tab 21a may be integrated with the positive electrode current collector 21.
[0031] Examples of materials for the insulating member 23 include insulating oxides such as alumina, resins such as polyvinylidene fluoride (PVDF), and rubbers such as styrene-butadiene rubber (SBR).
[0032] The negative electrode layer 3 includes a negative electrode current collector 31 and a negative electrode active material layer 32. The negative electrode current collector 31 is connected to the negative electrode tab 31a. The negative electrode tab 31a extends in the direction opposite to the positive electrode tab 21a (direction X in Figure 1). An insulating tape 35 is placed on a portion of the negative electrode tab 31a. The insulating tape 35 insulates the negative electrode tab 31a so that it does not come into contact with the positive electrode current collector 21 when the negative electrode tab 31a is bent toward the positive electrode layer 2. The thickness of the negative electrode current collector 31 may be, for example, in the range of 0.1 μm to 1 mm. The thickness of the negative electrode active material layer 32 may be, for example, in the range of 0.1 μm to 1 mm.
[0033] Examples of materials for the negative electrode current collector 31 include copper, copper alloys, nickel, and stainless steel.
[0034] The negative electrode active material layer 32 may occlude lithium ions or deposit lithium as lithium metal or a lithium alloy during charging of the lithium ion solid-state secondary battery 1, and release lithium ions during discharging. Lithium can be used as the material that deposits lithium ions as lithium metal during charging. As the material that occludes lithium ions during charging, metals that form an alloy with lithium and alloys containing such metals can be used. Examples of metals that form an alloy with lithium include Mg, Zn, Al, In, Si, Ge, Sn, Ag, Au, Pt, Pd, Pb, Sb, and Bi. In addition to the above, lithium titanate (Li4Ti5O 12 ) and other lithium transition metal oxides, transition metal oxides such as TiO2, Nb2O3 and WO3, metal sulfides, metal nitrides, and carbon materials such as graphite, soft carbon and hard carbon can be used. The negative electrode active material layer 32 may further contain materials that can be included in the negative electrode active material layer of a lithium ion solid-state secondary battery, such as a conductive aid, a binder, and a solid electrolyte. Alternatively, without providing the negative electrode active material layer 32, lithium ions may be directly deposited as lithium metal on the negative electrode current collector 31.
[0035] Examples of the material of the negative electrode tab 31a include copper, copper alloys, nickel, and stainless steel. The negative electrode tab 31a may be integral with the negative electrode current collector 31.
[0036] The solid electrolyte layer 4 has a two-layer structure in which a first solid electrolyte layer 41 disposed on the positive electrode layer 2 side and a second solid electrolyte layer 42 disposed on the negative electrode layer 3 side are laminated. The first solid electrolyte layer 41 contains a first solid electrolyte, and the second solid electrolyte layer 42 contains a second solid electrolyte.
[0037] The ratio D50_2 / D50_1 of the average particle diameter D50_2 of the second solid electrolyte to the average particle diameter D50_1 of the first solid electrolyte is set to be in the range of 1.0 or more and 10 or less. The average particle diameter D50 is the particle diameter at which the cumulative value reaches 50% in the cumulative volume particle size distribution curve under the sieve.
[0038] The ratio D50_2 / D50_1 may be in the range greater than 1.0 and less than or equal to 10. When the ratio D50_2 / D50_1 exceeds 1.0, the first solid electrolyte becomes finer than the second solid electrolyte, and its specific surface area increases, making it easier for the solid electrolytes to adhere to each other. As a result, the first solid electrolyte layer 41 has relatively higher lithium ion conductivity and improved strength compared to the second solid electrolyte. Due to the increased lithium ion conductivity, lithium ions are less likely to precipitate inside the first solid electrolyte layer 41, and short circuits in the solid electrolyte layer 4 become less likely. On the other hand, the second solid electrolyte becomes coarser than the first solid electrolyte, and the gaps between the solid electrolytes become wider. As a result, the second solid electrolyte layer 42 becomes relatively more deformable and has improved toughness compared to the first solid electrolyte layer 41. The increased deformability of the second solid electrolyte layer 42 enhances its volume expansion mitigation function and cushioning function. To improve the lithium ion conductivity of the first solid electrolyte layer 41 and the deformability of the second solid electrolyte layer 42, the ratio D50_2 / D50_1 may be in the range of, for example, 2.0 or more and 5.0 or less.
[0039] The average particle size D50_1 of the first solid electrolyte may be, for example, in the range of 0.1 μm or more and less than 1.0 μm. The average particle size D50_2 of the second solid electrolyte may be, for example, in the range of 2.0 μm or more and 5.0 μm or less.
[0040] The particle size D10_1 of the first solid electrolyte may be less than 0.5 μm. The particle size D10 is the particle size at which the cumulative value in the cumulative volume particle size distribution curve below the sieve becomes 10%. A small D10 means that there is a large proportion of fine particles. A larger proportion of fine particles increases the specific surface area, thus improving adhesion. From the viewpoint of improving the conductivity and strength of lithium ions in the first solid electrolyte layer 41, it is preferable that the particle size D10_1 of the first solid electrolyte be small. The particle size D10_1 of the first solid electrolyte may be, for example, in the range of 0.01 μm or more and 0.4 μm or less. The ratio D10_1 / D50_1 of the particle size D10_1 to the average particle size D50_1 of the first solid electrolyte may be, for example, in the range of 0.1 or more and 0.7 or less.
[0041] The particle size D90_2 of the second solid electrolyte may be 5.0 μm or larger. The particle size D90 is the particle size at which the cumulative value in the cumulative volume particle size distribution curve below the sieve reaches 90%. A larger D90 means that there is a larger proportion of coarse particles. A larger proportion of coarse particles widens the gaps between solid electrolytes, resulting in lower adhesion. From the viewpoint of improving the deformability and toughness of the second solid electrolyte layer 42, a larger particle size D90_2 of the second solid electrolyte is preferable. The particle size D90_2 of the second solid electrolyte may be, for example, in the range of 5.0 μm to 15 μm. The ratio D90_2 / D50_2 of the particle size D90_2 to the average particle size D50_2 of the second solid electrolyte may be, for example, in the range of 2.0 to 5.0.
[0042] The particle size distributions of the first and second solid electrolytes were measured using laser diffraction and scattering methods.
[0043] The ratio S1 / S2 of the specific surface area S1 of the first solid electrolyte to the specific surface area S2 of the second solid electrolyte may be, for example, within the range of 1.0 to 30.0. The specific surface area S1 of the first solid electrolyte may be, for example, 10 m². 2 / g or more 30m 2 It may be within the range of less than or equal to / g, and may be between 2.0 and 4.0. The specific surface area S2 of the second solid electrolyte is, for example, 1m². 2 / g or more 10m2 It may be within the range of / g or less. The specific surface area of the first solid electrolyte and the second solid electrolyte was measured by the BET method using nitrogen gas.
[0044] The ratio T2 / T1 of the thickness T1 of the first solid electrolyte layer 41 to the thickness T2 of the second solid electrolyte layer 42 is preferably greater than 1 and less than or equal to 100. The thickness T1 of the first solid electrolyte layer 41 may be in the range of, for example, 1 μm to 10 μm. Having the thickness T1 of the first solid electrolyte layer 41 within this range improves the lithium ion conductivity of the solid electrolyte layer 4. The thickness T2 of the second solid electrolyte layer 42 may be in the range of, for example, 10 μm to 100 μm. Having the thickness T2 of the second solid electrolyte layer 42 within this range improves the shape stability and toughness of the solid electrolyte layer 4.
[0045] The ratio P1 / P2 between the porosity P1 of the first solid electrolyte layer 41 and the porosity P2 of the second solid electrolyte layer 42 may be less than 1, for example, and may be in the range of 0.1 to 0.9. The porosity P1 of the first solid electrolyte layer 41 may be less than 1%, for example, and may be in the range of 0.1% to 0.99%. The porosity P2 of the second solid electrolyte layer 42 may be 1% or more, for example, and may be in the range of 2% to 5%.
[0046] The first solid electrolyte layer 41 and the second solid electrolyte layer 42 may further contain materials that can be included in the solid electrolyte layer of a lithium-ion solid-state secondary battery, such as a binder.
[0047] The ratio W1 / W2 of the mass content W1 of the first solid electrolyte in the first solid electrolyte layer 41 to the mass content W2 of the second solid electrolyte in the second solid electrolyte layer 42 is set to be greater than 1.0 and less than or equal to 1.2. The mass content W1 of the first solid electrolyte may be, for example, 97% by mass or more. Alternatively, the mass content W1 of the first solid electrolyte may be less than 100% by mass, 99.9% by mass or less, or 99.5% by mass or less. The mass content W1 of the second solid electrolyte may be, for example, 81% by mass or more. Alternatively, the mass content W2 of the second solid electrolyte may be less than 100% by mass, 99.9% by mass or less, 99.5% by mass or less, or 98% by mass or less.
[0048] When the ratio W1 / W2 exceeds 1.0, the solid electrolyte content of the first solid electrolyte layer 41 is higher than that of the second solid electrolyte layer, so the solid electrolytes in the first solid electrolyte layer 41 adhere to each other more easily than those in the second solid electrolyte layer 42. As a result, the lithium ion conductivity of the first solid electrolyte layer 41 is relatively higher and its strength is improved compared to the second solid electrolyte. Due to the increased lithium ion conductivity, lithium ions are less likely to precipitate inside the first solid electrolyte layer 41, and short circuits in the solid electrolyte layer 4 are less likely to occur. On the other hand, the second solid electrolyte layer contains more material other than solid electrolyte (binder) than the first solid electrolyte layer 41. As a result, the second solid electrolyte layer 42 is relatively more deformable and its toughness is improved compared to the first solid electrolyte layer 41. The increased deformability of the second solid electrolyte layer 42 improves its volume expansion mitigation function and cushioning function.
[0049] The materials for the first and second solid electrolytes are not particularly limited and can be any material that can be used as an electrolyte in a lithium-ion solid-state secondary battery. Examples include inorganic solid electrolytes such as sulfide solid electrolyte materials, oxide solid electrolyte materials, halide solid electrolytes, and lithium-containing salts, as well as polymer-based solid electrolytes such as polyethylene oxide. The materials for the first and second solid electrolytes may be the same or different. One type of solid electrolyte may be used alone, or two or more types may be used in combination.
[0050] Examples of binders include fluorine-based polymers, nitrile-based polymers, polyester-based polymers, acrylic acid-based polymers, cellulose-based polymers, styrene-based polymers, styrene-butadiene-based polymers, vinyl acetate-based polymers, urethane-based polymers, and fluoroethylene-based polymers. Among these binders, fluorine-based polymers are preferred. An example of a fluorine-based polymer is PVDF (polyvinylidene fluoride).
[0051] As a method for manufacturing the lithium-ion solid-state secondary battery 1, for example, a method can be used in which a solid electrolyte layer 4 and a negative electrode layer 3 are laminated in that order on the surface of the positive electrode layer 2. As a method for laminating the solid electrolyte layer 4 on the positive electrode layer 2, a transfer method or a coating method can be used. The transfer method involves preparing a transfer sheet by laminating the object to be transferred on a support sheet, joining the object to be transferred and the object to be transferred on the transfer sheet by a pressing method, and then peeling off the support sheet. For example, as a solid electrolyte layer transfer sheet, a second solid electrolyte layer 42 and a first solid electrolyte layer 41 may be prepared by laminating them in that order on a support sheet, and the positive electrode layer 2 and the first solid electrolyte layer 41 of the solid electrolyte layer transfer sheet may be joined. Alternatively, a lithium-ion solid-state secondary battery 1 may be manufactured by preparing a positive electrode layer 2 with the first solid electrolyte layer 41 transferred and laminated, and a negative electrode layer 3 with the second solid electrolyte layer 42 transferred and laminated, and then laminating them by pressing. The coating method involves applying a coating solution containing the object to be coated to the object to be coated, and then drying the resulting coating film. As a coating solution for forming a solid electrolyte layer, a first coating solution containing a first solid electrolyte layer material and a second coating solution containing a second solid electrolyte layer material may be prepared. The first coating solution may be applied to the positive electrode layer 2 to form a first solid electrolyte layer 41, and then the second coating solution may be applied to the first solid electrolyte layer 41 to form a second solid electrolyte layer 42. Alternatively, a lithium-ion solid-state secondary battery 1 may be manufactured by preparing a stack of a positive electrode layer 2 coated with the first solid electrolyte layer 41 and a negative electrode layer 3 coated with the second solid electrolyte layer 42, and then stacking them by press bonding.
[0052] Furthermore, as a method for manufacturing the lithium-ion solid-state secondary battery 1, a method can be used in which a solid electrolyte layer 4 and a positive electrode layer 2 are laminated on the surface of the negative electrode layer 3 in that order. As a method for laminating the solid electrolyte layer 4 onto the negative electrode layer 3, a transfer method or a coating method can be used. In the case of the transfer method, a solid electrolyte layer transfer sheet may be used in which a first solid electrolyte layer 41 and a second solid electrolyte layer 42 are laminated on a support sheet in that order, and the negative electrode layer 3 and the second solid electrolyte layer 42 of the solid electrolyte layer transfer sheet may be joined. In the case of the coating method, a second coating solution may be applied to the negative electrode layer 3 to form the second solid electrolyte layer 42, and then a first coating solution may be applied to the second solid electrolyte layer 42 to form the first solid electrolyte layer 41. As a method for laminating the positive electrode layer 2 onto the solid electrolyte layer 4, a pressing method can be used.
[0053] Furthermore, as a method for manufacturing the lithium-ion solid-state secondary battery 1, a method can be used in which a solid electrolyte layer 4 and a negative electrode layer 3 are laminated on the surface of the positive electrode layer 2 in that order. As a method for laminating the solid electrolyte layer 4 onto the positive electrode layer 2, a transfer method or a coating method can be used. In the case of the transfer method, a solid electrolyte layer transfer sheet may be used in which a first solid electrolyte layer 41 and a second solid electrolyte layer 42 are laminated on a support sheet in that order, and the first solid electrolyte layer 41 of the positive electrode layer 2 and the solid electrolyte layer transfer sheet may be transferred. In the case of the coating method, a first coating solution may be applied to the positive electrode layer 2 to form the first solid electrolyte layer 41, and then a second coating solution may be applied to the first solid electrolyte layer 41 to form the second solid electrolyte layer 42. As a method for laminating the negative electrode layer 3 onto the solid electrolyte layer 4, a pressing method can be used.
[0054] In the lithium-ion solid-state secondary battery 1 of this embodiment, which has the above configuration, the first solid electrolyte layer 41 has a higher mass content of solid electrolyte compared to the second solid electrolyte layer 42, and the solid electrolytes adhere more strongly to each other, resulting in higher lithium-ion conductivity and improved strength. On the other hand, the second solid electrolyte layer 42 can have a higher mass content of components other than solid electrolyte (e.g., binder) compared to the first solid electrolyte layer 41, so it becomes more deformable and its toughness is improved. Therefore, the lithium-ion solid-state secondary battery 1 of this embodiment (1) achieves an even higher level of balance between battery cell performance such as short-circuit prevention and improved durability, and structural integrity such as strength and toughness.
[0055] The lithium-ion solid-state secondary battery of the present invention is not limited to the lithium-ion solid-state secondary battery 1 of the above-described embodiment. For example, in the lithium-ion solid-state secondary battery 1 of this embodiment, the positive electrode layer 2, the solid electrolyte layer 4, and the negative electrode layer 3 are stacked in this order, but the structure of the lithium-ion solid-state secondary battery 1 is not limited to this. In the lithium-ion solid-state secondary battery 1 of this embodiment, the second solid electrolyte layer 42 on the negative electrode layer 3 side is easily deformable, and the second solid electrolyte layer 42 and the negative electrode layer 3 can be tightly bonded with high adhesion force. The lithium-ion solid-state secondary battery 1 may have an intermediate layer to improve the balance between battery cell performance such as short-circuit prevention and improved durability, and structural integrity such as strength and toughness at a higher level.
[0056] The intermediate layer may be a layer that has the function of uniformly moving lithium ions across the entire surface of the negative electrode layer 3 during charging. The thickness of the intermediate layer 5 is, for example, in the range of 0.3 μm to 10 μm.
[0057] The materials constituting the intermediate layer are not particularly limited, but examples include metals that can be alloyed with lithium and amorphous carbon. Examples of metals that can be alloyed with lithium include Mg, Zn, Al, In, Si, Ge, Sn, Ag, Au, Pt, Pd, Pb, Sb, and Bi. The metals that can be alloyed with lithium may be nanoparticles. Examples of amorphous carbon include carbon blacks such as acetylene black, furnace black, and Ketjen black, as well as coke and activated carbon. Amorphous carbon may be gas-phase carbon fiber (VGCF), easily graphitizable carbon (soft carbon), hard carbon, CNT (carbon nanotubes), fullerene, or graphene. The intermediate layer may contain a binder in addition to the above materials.
[0058] Amorphous carbon may be either easily graphitizable carbon (soft carbon) or difficult-to-graphitize carbon (hard carbon). Amorphous carbon can be any allotrope of carbon that does not exhibit a clear crystalline state, and may even be an aggregate of fine graphite crystals. Specific examples of amorphous carbon include carbon blacks such as acetylene black, furnace black, and Ketjen black, as well as coke, activated carbon, carbon nanotubes (CNTs), fullerenes, and graphene.
[0059] As the metal included in the intermediate layer, particles of metals that form an alloy with lithium can be used. Examples of metals that form alloys with lithium include Mg, Zn, Al, In, Si, Ge, Sn, Ag, Au, Pt, Pd, Pb, Sb, and Bi.
[0060] The intermediate layer may contain a binder in addition to the above-mentioned substances. The binder used in the solid electrolyte layer 4 can be used. However, the binder used in the intermediate layer and the binder used in the solid electrolyte layer 4 may be the same or different.
[0061] The intermediate layer can be arranged, for example, by laminating the intermediate layer onto the surface of the solid electrolyte layer 4, and then laminating the negative electrode layer 3 onto the surface of the intermediate layer. Transfer methods or coating methods can be used to laminate the intermediate layer 5 onto the surface of the solid electrolyte layer 4. Pressing methods can be used to laminate the negative electrode layer 3 onto the surface of the intermediate layer. Furthermore, there are no particular restrictions on the manufacturing method of the lithium-ion solid-state secondary battery in which the intermediate layer is arranged. For example, a positive electrode layer 2, a solid electrolyte layer 4, an intermediate layer, and a negative electrode layer 3 may be prepared separately, and each of these layers may be laminated and bonded. There are no particular restrictions on the bonding order of each layer. For example, a bonded body in which the positive electrode layer 2 and the first solid electrolyte layer 41 are bonded together, and a bonded body in which the second solid electrolyte layer 42, the intermediate layer, and the negative electrode layer 3 are bonded together, or a bonded body in which the positive electrode layer 2 and the solid electrolyte layer 4 are bonded together, and a bonded body in which the intermediate layer and the negative electrode layer 3 are bonded together. [Examples]
[0062] The present invention will be described below with reference to examples, but the present invention is not limited to these examples.
[0063] [Example 1] (1) Fabrication of the positive electrode layer A 15 μm thick aluminum foil was prepared as the positive electrode current collector. 80 parts by mass of lithium nickel cobalt manganese composite oxide (NCM712) was mixed as the positive electrode active material, 17 parts by mass of argyrodite-type sulfide solid electrolyte as the solid electrolyte material, 2 parts by mass of carbon black as a conductive additive, and 1 part by mass of a fluorine-based rubber binder as a binder. The resulting mixture was dispersed in 43 parts by mass of butyl butyrate to prepare a positive electrode active material layer slurry. The obtained positive electrode active material layer slurry was applied to both sides of the positive electrode current collector, with a dry basis weight of 27 mg / cm². 2 The material was coated using a bar coater, dried, and pressed to form a positive electrode active material layer with a thickness of 80-90 μm, thereby creating the positive electrode layer.
[0064] (2) Preparation of a solid electrolyte layer transfer sheet Two types of argyrodite-type sulfide solid electrolytes (first solid electrolyte, second solid electrolyte) were prepared as solid electrolytes. The particle size distribution, tap density, and specific surface area of the prepared solid electrolytes are shown in Table 1 below. The particle size distribution was measured by laser diffraction scattering in accordance with JIS Z 8825:2013. The tap density was measured by a tapping device in accordance with JIS Z 2512:2012. The specific surface area was measured by the BET method using nitrogen gas in accordance with JIS Z 8830:2013.
[0065] [Table 1]
[0066] 97.00 parts by mass of the second solid electrolyte and 3.00 parts by mass of an SBR-based binder were mixed. The resulting mixture was dispersed in a solvent to prepare a second solid electrolyte slurry. The obtained second solid electrolyte slurry was applied to the surface of a support sheet and dried to form a second solid electrolyte layer with a solid electrolyte content of 97.00% by mass.
[0067] A mixture of 98.70 parts by mass of the first solid electrolyte and 1.30 parts by mass of an SBR-based binder was prepared. The resulting mixture was dispersed in a solvent to prepare a first solid electrolyte slurry. The obtained first solid electrolyte slurry was applied to the surface of the second solid electrolyte layer and dried to form a first solid electrolyte layer with a solid electrolyte content of 98.70% by mass. In this way, a solid electrolyte layer transfer sheet with a two-layer structure was prepared on the surface of the support sheet, in which the second solid electrolyte layer and the first solid electrolyte layer were laminated in that order.
[0068] (4) Fabrication of the negative electrode layer A 10 μm thick copper foil was prepared as the negative electrode current collector. A 6.5 μm thick metallic lithium foil was laminated onto the surface of the copper foil to create the negative electrode layer.
[0069] (5) Fabrication of lithium-ion solid-state secondary batteries The first solid electrolyte layer of the solid electrolyte layer transfer sheet was superimposed on the surface of the positive electrode active material layer of the positive electrode layer, and bonded using a roll press device under bonding pressure of 800 MPa and bonding temperature of room temperature. Then, the support sheet of the solid electrolyte layer transfer sheet was peeled off to obtain a positive electrode layer-solid electrolyte layer bond. Next, the second solid electrolyte layer of the solid electrolyte layer transfer sheet was superimposed on the surface of the negative electrode active material layer of the negative electrode layer, and transferred using a roll press device under bonding pressure of 200 MPa and bonding temperature of room temperature. Then, the support sheet of the solid electrolyte layer transfer sheet was peeled off to obtain a negative electrode layer-solid electrolyte layer bond. Next, the positive electrode layer and the negative electrode layer-solid electrolyte layer bond were bonded using a uniaxial forming press device at a bonding pressure of 120 MPa for 1 minute, and then pressurized using a roll press device at a bonding pressure of 400 MPa to produce an electrode laminate. The resulting electrode stack was housed in an aluminum laminate film casing to fabricate a lithium-ion solid-state secondary battery. Buffer materials were placed on both the negative electrode and positive electrode sides, and the stack was restrained under a restraining pressure of 3 MPa.
[0070] [Examples 2-4, Comparative Examples 1-3] Solid electrolyte layer transfer sheets were prepared by varying the solid electrolyte content of the first and second solid electrolyte slurries, as shown in Table 1 below. Then, a lithium-ion solid-state secondary battery was prepared in the same manner as in Example 1, except that these sheets were used.
[0071] [evaluation] The electrode stacks and lithium-ion solid-state secondary batteries obtained in Examples 1-4 and Comparative Examples 1-3 were used for the following evaluations.
[0072] (Thickness of the solid electrolyte layer, porosity, and presence or absence of cracks) The lithium-ion solid-state secondary batteries obtained in Examples 1-3 and Comparative Examples 1-3 were removed from the restraining fixture. The removed lithium-ion solid-state secondary batteries were placed in a glove box and disassembled, and the electrode stack was recovered. The recovered electrode stack was cut, and the cut surface was surface-treated using a CP processing machine and a FIB processing machine. The cut surface of the electrode stack after surface treatment was observed using an SEM, and cross-sectional SEM images were obtained at magnifications of 1000 to 2500x. From the obtained cross-sectional SEM images, the thickness and porosity of the solid electrolyte layer were measured, and the presence or absence of cracks was checked. The measurement of porosity and the check for the presence or absence of cracks were performed as follows. The results, along with the type of solid electrolyte and electrolyte content of the solid electrolyte layer, are shown in Table 2.
[0073] Porosity was measured using the image analysis software ImageJ. Cross-sectional SEM images of the solid electrolyte layer were binarized using ImageJ to separate the voids from the rest of the layer. The area of the voids was measured, and the porosity was defined as the percentage of the area of the voids relative to the total area of the solid electrolyte layer in the observed cross-sectional image. If there were multiple solid electrolyte layers, the porosity was measured for each layer. In addition, 3 to 6 cross-sectional SEM images were used, and the average value was used as the porosity.
[0074] The presence or absence of cracks was visually confirmed from cross-sectional SEM images. A "○" was used to indicate no cracks, and a "×" was used to indicate cracks. In cases where multiple solid electrolyte layers were present, a "×" was used if a crack was found in one of the solid electrolyte layers.
[0075] (Battery performance of lithium-ion solid-state rechargeable batteries) The lithium-ion solid-state secondary batteries obtained in Examples 1-4 and Comparative Examples 1-2 were evaluated for their battery performance using a charge / discharge device and an impedance measuring device. The state of the solid electrolyte layer of the lithium-ion solid-state secondary batteries was also observed after evaluation to check for defects. Note that the lithium-ion solid-state secondary battery in Comparative Example 3, which showed cracks in the solid electrolyte layer, was not evaluated for battery performance. Battery performance was measured by initial voltage and DCR resistance during 10s discharge. A short circuit was determined to have occurred if the initial voltage was 2.0V or less, or if the DCR resistance was 0V. The results are shown in Table 3.
[0076] (State of the solid electrolyte layer of the lithium-ion solid-state secondary battery after evaluation) After evaluating the battery performance, the lithium-ion solid-state secondary battery was removed from the restraint jig. The removed lithium-ion solid-state secondary battery was placed in a glove box and disassembled, and the electrode stack was recovered. The recovered electrode stack was cut, and the cut surface was processed using a CP processing machine and a FIB processing machine. Subsequently, the cut surface of the electrode stack was observed using an SEM, and cross-sectional SEM images at magnifications of 1000 to 2500 times were obtained to check for the presence or absence of cracks in the cross-section of the solid electrolyte layer. In the cross-section of the solid electrolyte layer, those without cracks were marked with "○", and those with one or more cracks of 5 μm or longer were marked with "×". In the case of multiple solid electrolyte layers, if a crack was found in one solid electrolyte layer, it was marked with "×".
[0077] (Capacity retention rate and charge / discharge efficiency of lithium-ion solid-state rechargeable batteries) The lithium-ion solid-state secondary battery obtained in Example 1 was subjected to charge-discharge tests using a charge-discharge device under the conditions of a current rate of 1 / 3 capacity rate and a voltage range of 3.7V to 4.0V. The ratio of the discharge capacity after 300 cycles to the initial discharge capacity was calculated as the capacity retention rate. The ratio of the discharge capacity to the charge capacity at 300 cycles was calculated as the charge-discharge efficiency. The results are shown in Table 3.
[0078] [Table 2]
[0079] [Table 3]
[0080] From the above results, it can be seen that the lithium-ion solid-state secondary batteries obtained in Examples 1 to 4, in which the ratio W1 / W2 of the mass content W1 of the first solid electrolyte in the first solid electrolyte layer and the mass content W2 of the second solid electrolyte in the second solid electrolyte layer falls within the range of the present invention, do not experience short circuits and exhibit low DCR resistance. Furthermore, the lithium-ion solid-state secondary battery obtained in Example 1 shows a charge-discharge efficiency of 100% after 300 cycles, demonstrating high cycle characteristics. This is because the solid electrolyte layer formed by laminating the first solid electrolyte layer and the second solid electrolyte layer, in which the above ratio W1 / W2 falls within the range of the present invention, exhibits excellent lithium-ion conductivity between the positive electrode layer and the negative electrode layer, as well as excellent shape stability and toughness.
[0081] On the other hand, the lithium-ion solid-state secondary battery obtained in Comparative Example 3, which used the first solid electrolyte layer alone, had a crack in the solid electrolyte layer immediately after manufacturing. This is because the first solid electrolyte layer alone is somewhat inferior in toughness. The lithium-ion solid-state secondary battery obtained in Comparative Example 2, which used the second solid electrolyte layer alone, experienced a short circuit. This is because the second solid electrolyte layer alone is somewhat inferior in rigidity and shape stability. The lithium-ion solid-state secondary battery obtained in Comparative Example 1, where the ratio W1 / W2 was 1, developed cracks after DCR measurement. This is because when cracks occurred in the solid electrolyte layer on the positive electrode side due to stress caused by lithium deposition, the solid electrolyte layer on the negative electrode side had less difference in toughness and rigidity compared to the solid electrolyte layer on the positive electrode side, and therefore could not suppress the propagation of cracks in the solid electrolyte layer on the negative electrode side. [Explanation of Symbols]
[0082] 1. Lithium-ion solid-state rechargeable battery 2 Positive electrode layer 21 Positive electrode current collector 21a Positive Tab 22 Cathode active material layer 23 Insulating material 3. Negative electrode layer 31 Negative electrode current collector 31a Negative electrode tab 32 Negative electrode active material layer 35 Insulating Tape 4 Solid electrolyte layer 41 First solid electrolyte layer 42 Second solid electrolyte layer
Claims
1. It includes a positive electrode layer, a negative electrode layer, and a solid electrolyte layer interposed between the positive electrode layer and the negative electrode layer. The solid electrolyte layer is a laminate in which a first solid electrolyte layer disposed on the positive electrode layer side and a second solid electrolyte layer disposed on the negative electrode layer side are stacked. The first solid electrolyte layer comprises a first solid electrolyte, and the second solid electrolyte layer comprises a second solid electrolyte. The ratio D50_2 / D50_1 of the average particle diameter D50_2 of the second solid electrolyte to the average particle diameter D50_1 of the first solid electrolyte is within the range of 1.0 or more and 50.0 or less. A lithium-ion solid-state secondary battery in which the ratio W1 / W2 of the mass content W1 of the first solid electrolyte in the first solid electrolyte layer to the mass content W2 of the second solid electrolyte in the second solid electrolyte layer is greater than 1.0 and less than or equal to 1.
2.
2. The lithium-ion solid secondary battery according to claim 1, wherein the ratio D50_2 / D50_1 is in the range of 2.0 or more and 10.0 or less.
3. The lithium-ion solid-state secondary battery according to claim 1, wherein the average particle size D50_1 of the first solid electrolyte is in the range of 0.1 μm or more and less than 1.0 μm, and the average particle size D50_2 of the second solid electrolyte is in the range of 1.0 μm or more and 5.0 μm or less.
4. The lithium-ion solid-state secondary battery according to claim 1, wherein the particle size D10_1 of the first solid electrolyte is less than 1.0 μm, and the particle size D90_2 of the second solid electrolyte is 5.0 μm or more.
5. The lithium-ion solid-state secondary battery according to claim 1, wherein the ratio S1 / S2 of the specific surface area S1 of the first solid electrolyte to the specific surface area S2 of the second solid electrolyte is in the range of 1.0 or more and 30.0 or less.
6. The lithium-ion solid-state secondary battery according to claim 1, wherein the porosity P1 of the first solid electrolyte layer is less than 1%, and the porosity P2 of the second solid electrolyte layer is 1% or more.
7. The lithium-ion solid-state secondary battery according to claim 1, wherein the thickness T1 of the first solid electrolyte layer and the thickness T2 of the second solid electrolyte layer are different.
8. The lithium-ion solid-state secondary battery according to claim 7, wherein the ratio T2 / T1 of the thickness T1 of the first solid electrolyte layer to the thickness T2 of the second solid electrolyte layer is in the range of greater than 1 and less than or equal to 100.
9. The lithium-ion solid-state secondary battery according to claim 1, characterized in that the negative electrode layer contains lithium metal or a lithium alloy.
Citation Information
Patent Citations
All-solid battery and manufacturing method thereof
JP2023009988A
All-solid-state batteries
JP2023524296A
Solid electrolyte sheet, manufacturing method for same, and lithium secondary battery comprising same
WO2024111841A1